PENINGKATAN CIVIC SKILLS SISWA MELALUI MODEL PEMBELAJARAN INKUIRI BEBAS YANG DIMODIFIKASI PADA MATA PELAJARAN PPKN KELAS XI IPS DI SMA SWASTA ISLAM JAUHARUL FALAH AL-ISLAMY MUARO JAMBI: PENINGKATAN CIVIC SKILLS SISWA MELALUI MODEL PEMBELAJARAN INKUIRI BEBAS YANG DIMODIFIKASI PADA MATA PELAJARAN PPKN KELAS XI IPS DI SMA SWASTA ISLAM JAUHARUL FALAH AL-ISLAMY MUARO JAMBI - Aprilia, Dira; Irwan, Irwan (Citizenship Education, Faculty of Education, Jambi University, 2024)
The purpose of this study is to improve students' Civic Skills through the application of the Modified Free Inquiry Learning Model in class XI IPS 1 SMA Swasta Islam Jauharul Falah Al-Islamy. The design of this study is to use Classroom Action Research used by teachers during learning. The procedure of this study is designed for three cycles, each cycle of which is carried out in three face-to-face meetings. The action plan for each cycle in this study consists of four stages: 1. Planning Stage, 2. Action Implementation Stage, 3. Observation and Evaluation, 4. Analysis and Reflection Stage. Based on research data obtained from the use of teacher activity observation sheets, student activity observation sheets, and student Civic Skills assessment sheets. With a success criterion of 75%. Which is the result of students' Civic Skills in Cycle I Civic Skills with a total of only 40%. And the details per parameter of Civic Skills in cycle II are 61%. And in cycle III the details of the percentage of students' civic skills are 77%. It can be concluded that the Modified Free Inquiry Learning Model has an effect on improving students' Civic Skills.